Short Term Exposure to Heat and Sediment Triggers Changes in Coral Gene Expression and Photo-Physiological Performance - Poquita-Du, Rosa Celia; Huang, Danwei; Chou, Loke Ming; Mrinalini,; Todd, Peter A. (Frontiers in Marine Science, 2019)
Abstract Corals are known to exhibit a suite of mechanisms for survival under stressful conditions with the help of their endosymbiotic Symbiodiniaceae. However, exactly how the host animal responds to varying environmental conditions remains unclear. In this study, we tested two relevant environmental factors that are known to have deleterious effects on corals: heat and sediment. We examined among-genotype responses of Pocillopora acuta to these factors with RNA-Seq in concert with widely-used tools for assessing the physiological conditions of corals. Heat and sediment treatments were applied in a 2 × 2 crossed experimental design: (1) ~30°C without sediment (control, “C”), (2) ~30°C with sediment (sediment-only, “S”), (3) ~32°C without sediment (heat-only, “H”), (4) ~32°C with sediment (heat + sediment, “H+S”) over four consecutive days (3-h daily exposure) in ex situ aquarium conditions. A clear differentiation in gene expression patterns was observed in corals exposed to heat alone and to heat with sediment, relative to the control treatment. Few transcripts (~3) were found to be differentially expressed for corals exposed to sediment only. The greater impact of heat was supported by the photo-physiological measurements that showed significant effects on maximum quantum yield and average symbiont density among genotypes of P. acuta. The combined effect of heat and sediment caused a greater reduction in average symbiont density than the effect of sediment alone. Furthermore, “H+S” disrupted the ability of corals to maintain processes involving assembly and disassembly of cilium which suggest a synergistic effect between the two factors. We also found that host-specific genes which were expressed differentially may not be related to their interactions with algal symbionts. Rather, these genes are involved in a variety of biological functions including, but not limited to, cilium biogenesis and degradation, cilia motility, innate and adaptive immune responses, cell adhesion and bone mineralization, and processes involved in the cell cycle. These results reflect the complex response of the host alone. Overall, our findings indicate that acute heat stress in tandem with sediment can depress photo-physiological performance and trigger considerable changes in host gene expression.